MODES OF SARS-COV-2 TRANSMISSION - Patel, Nilesh D.; Desai, Kairavi J.; Patel, Shirishkumar M. (Journal of Vocational Health Studies, 2021)
Background: On 12th December 2019, pneumonia of unknown etiology was reported in number of human cases from Wuhan, central China. On 11th February 2020, the WHO named the disease COVID-19, short for "COronaVIrus Disease 2019”. This COVID-19 out-break has grown substantially to that of pandemic nature currently. Close personal contact and respiratory droplets from sneezes and coughs of patient can disseminate SARS-CoV-2. The WHO continues to stress the usefulness of environmental cleaning and disinfection, frequent hand hygiene, respiratory etiquette. The WHO also suggests avoidance of close, unprotected contact and maintenance of physical distance with people having fever or respiratory symptoms. Purpose: To develop strategies for lowering transmission of COVID-19, development of ways for distinguishing the various modes of transmission such as urine and fecal samples is need of the hour. Review: In a clinical scenario where possibility of vertical transmission of Covid-19 is increasingly being reported and transplacental transmission of the SARS-COV-2 cannot be ruled out, medical fraternity requires more evidence on vertical transmission for better mother and newborn care. Conclusion: In order to study the vertical dissemination of SARS-CoV-2, the heath authorities should include additional examinations of maternal and newborn samples in standard treatment guideline for pregnant women.